Negative pressure wound therapy for surgical site infection after sternotomy and its role in preparing the wound for reconstruction - Eyal Schwartzmann; Micah Sy; Mehul Sharma; Bartosz Mańkowski; Marek Jemielity; Bartłomiej Perek (Termedia Publishing House, 2021)
Surgical site infection (SSI) involving the mediastinum after cardiac surgical procedures carried out through median sternotomy is associated with significant mortality and morbidity [1]. Up to now a few methods have been describe to treat such severe adverse events in the early postoperative period [2]. One of them is negative pressure wound therapy (NPWT) [3]. Since its introduction by Argenta and Morykwas, NPWT has been an efficacious method, in terms of improved early and long-term outcomes, of managing SSI after cardiac surgical procedures [4]. This method was also proved to be of paramount importance in assisting wound healing in subjects at the highest risk for developing SSI, such as obese, insulin-treated diabetic and chronic obstructive pulmonary disease (COPD) patients [3]. In some individuals it may enable the infected wound to be closed definitely by playing the role of the intermediate stage before either placing mattress adapting skin sutures or transferring different local free cutaneous flaps with/without muscle tissue.